Is Taylor's Rule Too Simple to be of Practical Use in a Small Open Economy Such as the Czech Republic? - Juračka, Tomáš; Mičúch, Marek, 1980-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2011)
The Taylor rule and its variants played a prominent role in the monetary policy discussion among theoreticians and practitioners for more almost two decades. The purpose of this thesis is to assess on the applicability of the simple instrument rules such as a classic Taylor's rule to the Czech economic environment which can be described as a small open economy with banking market specifically skewed by excess liquidity. The applicability is evaluated based on the variants of the Taylor rule and their effectiveness in describing the monetary policy of the central bank. The results of the models presented in this thesis are ambiguous. Traditional specification of the Taylor's rule is clearly unsuccessful in describing the behaviour of the Czech National Bank. However, if the models are altered to their historical variants containing only the information accessible at the time of decision making, their robustness and explanatory value increase significantly. Taking interest rate smoothing and exchange rate into consideration further improves the models. The policy behaviour of the Czech National Bank can be best described by the historical model with the one-year-ahead inflation prognosis, output gap, exchange rate and lagged target interest rate as explanatory variables. One of interesting results of this model is that the output gap does not play important role in the Czech National Bank decision making which is consistent with the opinions presented in the Czech National Bank Board Minutes.
Vedoucí práce: Marek Mičúch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses